BLOCKCHAIN TECHNOLOGY IN SUPPLY CHAIN ECONOMICS AND MANAGEMENT: APPLICATIONS, VALUE CREATION, AND IMPLEMENTATION CHALLENGES (International Congress on Economics, Management and Business Studies, 2026)
This article presents a systematic literature review examining blockchain technology applications in supply chain economics and management, with focus on value creation mechanisms, documented economic benefits, and implementation challenges in both advanced and emerging economy contexts. Publications from 2016 to 2024 indexed in Scopus, Web of Science, and supply chain management specialist databases were analysed. The review covers foundational blockchain concepts relevant to supply chain management, principal application domains including traceability, smart contracts, and decentralised finance, economic value creation through transparency and disintermediation, governance and standardisation challenges, and the applicability of blockchain supply chain solutions in Uzbekistan's agro-industrial and manufacturing sectors. The analysis demonstrates that blockchain supply chain implementations generate verifiable value through counterfeit reduction, compliance cost savings,
Keywords: and financing cost reductions, but face significant implementation barriers including scalability limitations, interoperability deficits, and ecosystem coordination challenges.